Demographic, Sociocultural, and Behavioral Predictors of Modern Contraceptive Uptake Among Couples in Northern Ghana [Response to Letter] - Allotey NK; Bosoka SA (Dove Medical Press, 2024)
Naa-Korkor Allotey,1,2 Samuel Adolf Bosoka3,4 1Ethics and Research Management Department, Research and Development Division, Ghana Health Service, Accra, Ghana; 2Department of Population, Family and Reproductive Health, School of Public Health, University of Ghana, Accra, Ghana; 3Disease Surveillance Unit, Volta Regional Health Directorate, Ghana Health Service, Ho, Ghana; 4Department of Epidemiology and Biostatistics, Fred N. Binka School of Public Health, University of Health and Allied Sciences, Ho, GhanaCorrespondence: Naa-Korkor Allotey, Email naa.korkorallotey@ghs.gov.gh; korkorallotey@gmail.com